Consumer Perception, Attitude And Purchase Intention Towards Halal Tourism Services In Non-Muslim Country: Malaysian Muslim Perspective - Ahmad, Russyazila (2014)
Halal tourism has become one of a new tourism products in the tourism industry that given significant impact to either Muslim or non-Muslim country. Lately the Halal tourism services are not only provided by Muslim countries, but Non-Muslim countries that do not have an appropriate Halal certification body are also claiming to provide Halal tourism service. This study will attempt to find out what is Muslim's in particular Malaysian Muslim's consumer perception and attitude towards Halal tourism services provided by NonMuslim country. The main objective of this study is to answer on how factors such as Halal food, Halal friendly hotels, Halal airlines, Halal Islamic package, Halal finance and Halal Standard provided by non-Muslim country have any impact to the consumer attitude and purchase intention to the service provided. This study is conducted in quantitative method using primary data; questionnaires. A total of 102 respondents from all over Malaysia had participated in this study.